Public key encryption in the cloud computing environments: trust and untrust - Nanang, Herlino; Durachman, Yusuf; Misman, Ahmad Fatzilah; Zulkifli, Zahidah; Sukmana, Husni Teja (IEEE, 2021)
With the development of data storage technology and the computerized process of an internet-based technology. Cloud computing systems allow users to store and process data virtually. Users also do not need to prepare a platform or supporting infrastructure, but only need to use existing platforms. For the establishment of a trust relationship between entities as an important part of establishing security mechanisms in the cloud computing environment. This article introduces a trust management model in cloud computing using public key encryption. Measurement and computation of trust, and the chain of trust where similarity of trust issues is recommended have been addressed to prevent fraudulent user behavior. This model is geared towards cloud users who make decisions about whether to use a cloud computing service provider by giving them confidence. The purpose of this article motivates us to try proposes new ideas and methods of trust management in cloud computing using public key encryption.